The influence of geometric parameters on strength properties of the aggregates used to produce asphalt mixtures - Bulevičius, Matas; Petkevičius, Kazys; Čirba, Stasys (Journal of Civil Engineering and Management, 2013)
Physical and mechanical properties of asphalt mixtures have a significant impact on a condition of fitted pavement, its stability and reliability during the entire period of its operation. These properties not only depend on bituminous binders chosen for an asphalt mixture and properties of mineral filler, but also on geometric and physical properties of the aggregate. An analysis of these indexes showed physical and geometrical indexes of aggregate of different origins (granite, dolomite and gravel). While researching mineral materials used for asphalt mixtures, the values of flakiness and shape index (FI and SI), impact value SZ and Los Angeles coefficient LA were determined. After calculations, the hypotheses for the average of flakiness and shape indexes of researched rocks (granite, dolomite and gravel) and proximity of dispersions were tested in order to determine the authenticity of geometric quality parameters and similarity of their sampling dispersion. Results of statistical data calculations determined a correlation between geometric parameters of researched aggregate FI and SI and geometrical, strength parameters of the aggregate. The hypotheses, whether research data of these indexes were distributed by normal distribution, were tested by drawing frequency histograms of granite, dolomite and gravel flakiness and shape indexes.